A School-Based Professional Learning Community Improving Equity and Inclusion for At-Risk Readers in French Immersion - Raymond, Krystina; George, Robert; Cadez, Ron; Follows, Michelle; Neveux, Nicole; Hipfner-Boucher, Kathleen; Genesee, Fred; Chen, Xi (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2024)
This longitudinal, mixed-methods study reports on the development and implementation of an early phonological awareness screening and intervention program for struggling emergent readers in a French immersion school in Manitoba. The program was created by a professional learning community made up of the school administrator, teachers, and clinical support staff. This paper describes the process of developing the phonological awareness program and the intervention itself. Forty-two children participated in the phonological awareness intervention that lasted 10 weeks. The intervention was given in English in kindergarten. Significant gains were found in the phonological awareness skills of the children who participated in the intervention. Results also indicated that children’s phonological awareness skills in English predicted their French reading levels in Grade 1. In addition, we provide insight into the roles played by key members of the school’s PLC through qualitative analysis of a series of semi-structured interviews. The work of the school’s professional learning community offers a model that may be implemented by other school teams to promote equity and accessibility for all learners in FI programs.